Paracrine IFN Response Limits ZIKV Infection in Human Sertoli Cells - Strange, Daniel P.; Jiyarom, Boonyanudh; Sadri-Ardekani, Hooman; Cazares, Lisa H.; Kenny, Tara A.; Ward, Michael D.; Verma, Saguna (Frontiers in Microbiology, 2021)
Zika virus (ZIKV) is unique among mosquito-borne flaviviruses in its ability to be sexually transmitted. The testes have been implicated as sites of long-term ZIKV replication, and our previous studies have identified Sertoli cells (SC), the nurse cells of the seminiferous epithelium that govern spermatogenesis, as major targets of ZIKV infection. To improve our understanding of the interaction of ZIKV with human SC, we analyzed ZIKV-induced proteome changes in these cells using high-throughput liquid chromatography-tandem mass spectrometry (LC-MS/MS). Our data demonstrated that interferon (IFN) signaling was the most significantly enriched pathway and antiviral proteins MX1 and IFIT1 were among the top upregulated proteins in SC following ZIKV infection. The dynamics between IFN response and ZIKV infection kinetics in SC remains unclear, therefore we further determined whether MX1 and IFIT1 serve as antiviral effectors against ZIKV. We found that increased levels of MX1 at the later time points of infection coincided with diminished ZIKV infection while the silencing of MX1 and IFIT1 enhanced peak ZIKV propagation in SC. Furthermore, although IFN-I exposure was found to significantly hinder ZIKV replication in SC, IFN response was attenuated in these cells as compared to other cell types. The data in this study highlight IFN-I as a driver of the antiviral state that limits ZIKV infection in SC and suggests that MX1 and IFIT1 function as antiviral effectors against ZIKV in SC. Collectively, this study provides important biological insights into the response of SC to ZIKV infection and the ability of the virus to persist in the testes.